Domestic Violence dalam AlQur’an (Analisis Penafsiran Muhammad Syahrur terhadap QS. An-Nisa’ Ayat 34) - Ramadani, Cindy Irawati (ALSYS, 2023)
Gender-based violence known as “domestic violence” refers to acts committed by people who are well known to the victim, are close to the victim, or live in the same house as the victim. Examples of domestic violence include acts committed by husbands against wives, fathers against children, and uncles against nephews, and so on. Domestic Violence can occur due to many factors that trigger it, for example, patriarchal culture and the nusyuz of a wife towards her husband which results in debates and even commits domestic violence. In the Qur'an the surah that discusses this case is surah An-Nisa' verse 34 which contains ways to deal with an nusyuz wife and a leadership position in the household. But even so in the Qur'an it is absolutely not justified to commit violence against a wife who is nusyuz. Whatever the form of violence and its causes, it is the duty and responsibility of all family members to continue to create a harmonious atmosphere in the household. Because tests and obstacles will always come in a relationship to test whether the relationship is appropriate or not to get to the heaven of Allah SWT.